Data Processing and Machine Learning for Assistive and Rehabilitation Technologies - Andrea Tigrini; Agnese Sbrollini; Alessandro Mengarelli (Bioengineering)
This Special Issue (SI), “Data Processing and Machine Learning for Assistive and Rehabilitation Technologies”, aimed to collect cutting-edge research papers that frame how data-driven approaches and machine learning techniques are advancing the field of assistive and rehabilitation technologies [...]